ENT 530 Social media report / Aida Nadhirah Ahmad Fuad - Ahmad Fuad, Aida Nadhirah (2021)
SoukkibyDhir is a small business owned by Aida Nadhirah binti Ahmad Fuad. The shop provides socks that are incredibly comfortable to wear. Appropriate for different events / services. The wearer's aura can be improved by very appealing color choices. Both walks of life have quite affordable rates. This business targets young females as their target audience. Hence, all SoukkibyDhir socks collection focuses on cute and colourful designs. Accordingly with their tagline “Be The Colourful You!”, SoukkibyDhir aims to supply comfy and colourful socks for young females to match with their styles. The products have a very affordable price range. For basic package socks it is only at RM 4.99 a pair. During sales, 3 pairs of socks are priced at only RM 10. While for the limited edition design one, the price range starts at RM 6.99. It is supply-on-demand stocks.